Implementación de un prototipo de una máquina lavadora de piezas automotrices hasta 20 kg de capacidad en el taller Velasco ubicado en la ciudad de Latacunga. - Pucuji Suquillo, Moises Hernan (2022)
The current thesis was carried through in the Latacunga city into "VELASCO" mechanical workshop, the workshop interest for building this machine arises to save times to save washing times washing and reduce costs into cleaning process the pieces. For machine implementation is considered the parameters such as the water and degreaser amount, whose is occupied for cleaning, as well as the pressure that supply by the pump to the sprinklers. Also, it was considered the structure design, which supports the storage tank, where it is made the mixture, further, the hydraulic part, whose allows the table rotation, the fluid heating system and a simple electrical system for the 20 kg washing process automotive parts, it was selected a KARCHER K2 model with a 10 MPa pressure and a 4.2 l/min flow rate that ensures the process parameters.